The Effect of Probiotic Supplement as Adjuvant Therapy on Dyspeptic Symptoms and Quality of Life during Helicobacter pylori Eradication Therapy in a Sample of Iraqi Patients with Peptic Ulcer Disease - Aseel Mohammed Ameen; Manal Khalid Abdulridha; Akram Ajeel Najeeb (College of Pharmacy / Mustansiriyah University, 2018)
Infection with Helicobacter pylori (H. pylori) had been associated with development of certain symptoms in addition to the use of standard eradication triple therapy has resulted in the increased incidence of undesirable side effects, which can lead to reduced compliance. Probiotics have been proposed to contribute to their efficacy in increasing H. pylori eradication and decreasing side effects when used together with eradication therapy. This study was intended to minimize the side effects of antibiotics therapy and the symptoms associated with peptic ulcer disease (PUD) and improving patient's quality of life (QOL). This interventional prospective randomized- controlled, open-label study was carried out on 77 patients diagnosed with positive H. pylori infection during the period from September 2017 to April 2018. The incidence and intensity of symptom score that caused by adverse effects of both infection and therapy were highly significantly decrease in terms of epigastric pain, bloating, flatulence, taste disturbance, loss of appetite, nausea, vomiting, and heartburn after 2 months of treatment within each study group correspondingly all domains of the quality of life were significantly improved in all patients after H. pylori eradication within each study group. From the present study concluded that the administra¬tion of probiotics as adjuvant to standard triple therapy may suggest a role in improving the symptoms and reduce the adverse effects accompanying with the eradication therapy for H. pylori thus improving patient's quality of life.